Association of c-reactive protein and uric acid with Type 2 diabetes (Dhaka University Journal of Biological Sciences, 2011)
Diabetes mellitus is a group of metabolic diseases characterized by high blood glucose levels that result from defects in insulin secretion or action or both. Some recent studies had shown that elevated level of C?reactive protein (CRP) and uric acid are involved in the pathogenesis of type 2 diabetes, regardless of other characteristics of subjects. Our aim was to investigate the association between CRP and uric acid levels with diabetes in Bangladeshi population. Two hundred type 2 diabetic subjects (male 110, female 90) and 60 non diabetic subjects (30 male, 30 female) were included in the study over six months. CRP and uric acid were measured by Latex Agglutination method and enzymatic colorimetric method, respectively. CRP was significantly higher (p < 0.01) in diabetic compared to non-diabetic subjects for both male and female subjects. The level of uric acid was also significantly higher in male and female diabetic subjects (p < 0.05 and p < 0.01) compared to non-diabetic subjects, respectively. In multiple regression analysis, CRP showed a positive association with uric acid and BMI in both diabetic and non-diabetic subjects. On the other hand, uric acid showed positive association with fasting blood sugar (FBS), diastolic blood pressure, HbA1c and CRP in case of diabetic subjects, but with age, BMI, CRP, HbA1c and creatinine in non-diabetic subject. Uric acid also shows a significantly (p < 0.001) positive Pearson correlation with CRP. These data strongly suggest that compared to non-diabetic subjects, diabetic subjects have significantly higher level of CRP and uric acid. Key words: C-reactive protein; Uric acid; Type 2 diabetes; Bangladeshi population DOI: http://dx.doi.org/10.3329/dujbs.v20i2.8980 DUJBS 2011; 20(2): 191-199